Gut‐Derived Serum Lipopolysaccharide is Associated With Enhanced Risk of Major Adverse Cardiovascular Events in Atrial Fibrillation: Effect of Adherence to Mediterranean Diet. Issue 6 (5th June 2017) - Pastori, Daniele; Carnevale, Roberto; Nocella, Cristina; Novo, Marta; Santulli, Maria; Cammisotto, Vittoria; Menichelli, Danilo; Pignatelli, Pasquale; Violi, Francesco
Abstract : Background: Gut microbiota is emerging as a novel risk factor for atherothrombosis, but the predictive role of gut‐derived lipopolysaccharide (LPS) is unknown. We analyzed (1) the association between LPS and major adverse cardiovascular events (MACE) in atrial fibrillation (AF) and (2) its relationship with adherence to a Mediterranean diet (Med‐diet). Methods and Results: This was a prospective single‐center study including 912 AF patients treated with vitamin K antagonists (3716 patient‐years). The primary end point was a composite of MACE. Baseline serum LPS, adherence to Med‐diet (n=704), and urinary excretion of 11‐dehydro‐thromboxane B2 (TxB2, n=852) were investigated. Mean age was 73.5 years; 42.9% were women. A total of 187 MACE (5.0% per year) occurred: 54, 59, and 74 in the first, second, and third tertile of LPS, respectively (log‐rank test P =0.004). Log‐LPS (hazard ratio 1.194, P =0.009), age (hazard ratio 1.083, P <0.001), and previous cerebrovascular (hazard ratio 1.634, P =0.004) and cardiac events (hazard ratio 1.822, P <0.001) were predictors of MACE. In the whole cohort, AF (versus sinus rhythm) (β 0.087, P =0.014) and low‐density lipoprotein cholesterol (β 0.069, P =0.049) were associated with circulating LPS. Furthermore, Med‐diet score (β −0.137, P <0.001) was predictive of log‐LPS, with fruits (β −0.083, P =0.030) and legumes (β −0.120, P =0.002) negatively associated with log‐LPS levels. Log‐LPS and log‐TxB2 were highly correlated (r=0.598, P <0.001). Log‐LPS (β 0.574, P <0.001) and Med‐diet score (β −0.218, P <0.001) were significantly associated with baseline urinary excretion of TxB2 . Conclusions: In this cohort of AF patients, LPS levels were predictive of MACE and negatively affected by high adherence to Med‐diet. LPS may contribute to MACE incidence in AF by increasing platelet activation.